Validation of performance of certified medical assistants in preschool vision screening examination - Adhikari, S; Shrestha, U (Nepalese Journal of Ophthalmology, 2011)
DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5264 Nepal J Ophthalmol 2011; 3(2): 128-133